HUBUNGAN ANTARA SELF-EFFICACY DAN MOTIVASI BERPRESTASI SISWA KELAS XI IPA DALAM MATA PELAJARAN KIMIA DI SMA NEGERI 3 PONTIANAK - Bellya Firsty Novanda (Jurnal Ilmiah Ar-Razi, 2018)
The students’ average score on Chemistry subject has still low. This has caused not only by the level of the difficulty but also the low of the students’ self-efficacy and motivation.  This  study  aimed  at  finding  out  the  students’  self-efficacy, motivation,  and the  correlation  of  self-efficacy  and  achievement  motivation  among  the  ninth  grade Science  class  students  of  SMA  Negeri  3  Pontianak.  Using  descriptive  correlational design,  as  many  as  66  students  of  the  ninth  grade  Science  class  participated  in  this study. The self-efficacy measurement was conducted by using self-efficacy scale which was adopted from the Bandura scale  with a reliability coefficient of 0.86, whereas, the achievement  motivation  measurement  conducted  by  using  achievement  motivation scale  based  on  The  Mehrabian  Achieving  Tendency  from  Mehrabian  1993  with  a consistency  internal  reliability  of  0.92.  The  study  reveals  that  53,03%  of  students obtained    medium    self-efficacy,  and  60,61%  of  students  students  had  average achievement  motivation.  The  Pearson  Product  Moment  correlation  test  indicated  that there was a positive and significant correlation between self-efficacy and achievement motivation by 0,278 which was considered into low category with  sig value (2-tailed) of 0.024. Keywords: Chemistry, Correlation, Achievement Motivation, Self-efficacy